2019
DOI: 10.18632/oncotarget.26892
|View full text |Cite
|
Sign up to set email alerts
|

Programmed cell death ligand 1 (PD-L1) blockade attenuates metastatic colon cancer growth in cAMP-response element-binding protein (CREB)-binding protein (CBP)/β-catenin inhibitor-treated livers

Abstract: Immune checkpoint blockade with specific antibodies can accelerate anti-tumor immunity, resulting in clinical responses in patients with various types of cancer. However, these antibodies achieve only partial tumor regression. Thus, a wide variety of treatment combinations based on programmed death-ligand 1 (PD-L1) pathway inhibition are under development to enhance such therapeutic effects. In this study, the effects of combination treatment using PRI-724, a selective inhibitor of CBP/β-catenin, and an anti-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Targeting CREB1 binding protein/β-catenin, combined with PD-1/PD-L1 blockade, has shown potential as a new therapeutic strategy for treating liver metastasis in CRC. 53 Further studies are needed on the role of CREB1 and TNF signaling in MSS cancers and their susceptibility to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting CREB1 binding protein/β-catenin, combined with PD-1/PD-L1 blockade, has shown potential as a new therapeutic strategy for treating liver metastasis in CRC. 53 Further studies are needed on the role of CREB1 and TNF signaling in MSS cancers and their susceptibility to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…We also quantified the Treg population by measuring co-expression of CD25 and FoxP3, but in contrast to other reports [ 14 , 35 ], we did not detect changes in the frequencies among treatment groups of this clearly detectable population that represented on average 3.5% of human TILs (Supplementary Fig 1 ). A previous report studying PRI-724, a CBP/β-catenin inhibitor, in a mouse model of colorectal cancer, observed increases in the Treg population with drug treatment, suggesting that a decrease in Tregs is not a consistent finding with β-catenin inhibition [ 37 ]. Our analysis of the myeloid populations showed that although they are underrepresented in general in humanized mice, we did observe substantial representation of these cells in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Cui et al has shown that ICG-001 effectively inhibited the metastatic progression of HCC tumors in both cell line and patient-derived xenograft mouse models [50]. Moreover, PRI-724, the derivative of ICG-001, was reported to induce CD8 + T-cells in ltrates and IFN-γ production in liver metastatic lesions in a mouse model of colon cancer with liver metastasis [51]. The combination treatment of anti-PD-L1 antibody and PRI-724 resulted in regression of tumor growth.…”
Section: Discussionmentioning
confidence: 99%